2009
DOI: 10.1007/s10551-009-0276-9
|View full text |Cite
|
Sign up to set email alerts
|

Role Conflict, Mindfulness, and Organizational Ethics in an Education-Based Healthcare Institution

Abstract: role conflict, mindfulness, ethical values, ethics codes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 77 publications
1
35
0
2
Order By: Relevance
“…The Studies have shown that mindfulness as a dynamic and active cognitive structure is able to affect people's response in stressful and emotional situation. By using informed attention, mind awareness makes people ready to respond to dangerous situations (Valentine, 2010). It is worth mentioning that Ndubisi (2012) www.ccsenet.org/gjhs Global Journal of Health Science Vol.…”
Section: Discussionmentioning
confidence: 99%
“…The Studies have shown that mindfulness as a dynamic and active cognitive structure is able to affect people's response in stressful and emotional situation. By using informed attention, mind awareness makes people ready to respond to dangerous situations (Valentine, 2010). It is worth mentioning that Ndubisi (2012) www.ccsenet.org/gjhs Global Journal of Health Science Vol.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Shapiro et al (2012) also found no correlation between moral reasoning and mindfulness instruction one month after completion of the training and only a minor correlation 2 months after. Interestingly, Valentine et al (2010) established that having a shared corporate code of ethics and ethical values were positively related to mindfulness suggesting an ethical organisational culture enhances an individual's capacity to be mindful but without a reciprocal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Originally conceived as having a presence of mind or an attentiveness to the present (Abe, 1993), in more recent times both the psychology and organisational literature have been combined to define it as "a state of mind or mode of practice that permits the questioning of expectations, knowledge and adequacy of routines in complex and not fully predictable social, technological, and physical settings" (Jordan et al, 2009, p. 466). As such, mindfulness is a useful attribute that enables people to better respond to their environment (Valentine et al, 2010). Moreover, similar to spirituality, everyone has the capacity for mindfulness (Ruedy & Schweitzer, 2010).…”
Section: Mindfulnessmentioning
confidence: 99%
See 2 more Smart Citations